E-CommerceDalam Perspektif Islam - Arie Rachmat Soenjoto (Islamic Economics Journal, 2015)
The rapid development of the media make the distance between the state seemed close to where a person can achive its objectives with a very short time a matter of second due to the electronic media such as television, telephone, internet and so forth. Companies have used media to the benefit of consumers, where consumers remain at home and transfer the agreed price through the bank. Although this transaction is going well, but the customers does not see a crystal clear, giving rise to dispute on both sides. Based on these problems researcher examined further to determine the legal sale and purchase through internet. At this study the author used observations and documentary were then assessed using the inductive method to explain clearly about buying and selling via internet, the deductive method to provide a legal basis boundaries syaria about buying and selling over the internet which is based on Al-Qur’an and AlHadits. In order to deliver to the conclusion in this study, researcher used an analytical and descriptive method to describe the process of buying and selling over the internet and the law as well as the benefits and riks posed belong. As known, sale and purchase will valid if it has fulfilled the whole pillars and conditions. Such consent and qobul called expression and desire. This expression can be realized with any show or words such as lafadz habits, work, gesture, or oral. Although between the seller and buyer does not meet in one place but the terms of the sale were met, than the selling is legitimate. Even the goods are not visible or are not present, then the seller must mention the nature or typical of goods and mention the amountour can describe it so that the sale and purchase of goods with the use of electronic media is a legitimate law. E-Commerce is nothing but as an intermediary that connects something that meant. Therefore buying and selling via internet can be allowed on the condition based on ethics purchase procedure and does not conflict with Islamic law.